Prostaglandin E-2 inhibits Paracoccidioides brasiliensis killing by human monocytes - Bordon, Ana Paula; Dias-Melicio, Luciane Alarcao; Acorci-Valerio, Michele Janegitz [UNESP]; Calvi, Sueli Aparecida; Serrao Peracoli, Maria Terezinha; Victoriano de Campos Soares, Angela Maria (Elsevier B.V., 2007)
Human monocytes lacked fungicidal activity against high virulence strain of Paracoccidioides brasiliensis, even after IFN-gamma activation. However, monocytes treated with indomethacin exhibited an effective killing against this fungus, suggesting a role of prostaglandin E-2 (PGE(2)) in the inhibition process. Thus, the purpose of this work was to determine whether the effect of PGE2 in fungicidal activity was related with decrease on H2O2 release, the metabolite involved in P. brasiliensis killing, and changes in the levels of TNF-alpha, IL-6 and IL-10. Human monocytes challenged with the fungus produced high PGE(2) levels, which in turn inhibited the fungicidal activity of these cells by reducing H2O2 and TNF-alpha production. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: prostaglandin E-2; H2O2; cytokines; monocytes; Paracoccidioides brasiliensis